Effect of drought stress on biochemical contents and proline metabolizing enzymes of Pennisetum glaucum L. - S. Suganthi; K. G. Sivagami; C. Maheswari; P. Manivannan (Innovations in Agriculture)
Drought stress is one of the major environmental problem affecting agricultural production in arid and semi-arid regions of the world. In present study, the effect of drought stress on Pennisetum glaucum L. (Pearl millet) plants was studied. The seed were sown in plastic pots from 30 days after sowing (DAS). The plants were treated with 3 DID (Days Interval Droughts), 4 DID, 5 DID and 6DID and 30th to 60th DAS. The plants samples were collected from 40th, 50th and 60th DAS. The biochemical like, protein content decreased to increasing drought stress to a larger extent when compared to control plants and also increased the amino acids and proline content to the larger extent with increasing DID when compared to control. The proline metabolizing enzyme like g-glutamyl kinase activity was increased and decreased proline oxidase activity on drought stressed plants.